The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/00288330909510017
|View full text |Cite
|
Sign up to set email alerts
|

Management strategy evaluation for rock lobster,Jasus edwardsii, off Victoria, Australia: Accounting for uncertainty in stock structure

Abstract: The management strategy evaluation (MSE) approach was used to evaluate management strategies based on the current method of stock assessment for rock lobster (Jasus edwardsii) off Victoria, Australia, and decision rules inferred from the management plan for Victorian rock lobster and past practice when selecting total allowable catches, TACs. The results are expressed in terms of whether it is possible to keep stocks above limit reference points with high probability and recover overexploited stocks to the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…There are a number of empirical studies specifically designed to examine the implications of stock structure uncertainty (IWC 1994;Dichmont et al 2006;Kell et al 2009;Punt & Hobday 2009), and while none have considered explicit economic implications, the work contained in this paper adds to the research that ignoring spatial structureboth demographic and fishery relatedcan have a profound impact. We found that the assumptions made about stock structure not only resulted in different bioeconomic TRPs (generally, smaller steady-state effort from the multistock models) but also different economic outcomes, although little evidence of differences in conservation-related outcomes was found.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of empirical studies specifically designed to examine the implications of stock structure uncertainty (IWC 1994;Dichmont et al 2006;Kell et al 2009;Punt & Hobday 2009), and while none have considered explicit economic implications, the work contained in this paper adds to the research that ignoring spatial structureboth demographic and fishery relatedcan have a profound impact. We found that the assumptions made about stock structure not only resulted in different bioeconomic TRPs (generally, smaller steady-state effort from the multistock models) but also different economic outcomes, although little evidence of differences in conservation-related outcomes was found.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although Butterworth and Punt () commented that there were very few operating models which accounted for spatial structure when they conducted their review in 1998, subsequently Punt et al . (), IWC (,b, , ), Punt and Hobday () and Carruthers et al . () have all developed operating models which can, to some extent, account for spatial structure.…”
Section: Best Practices For Msementioning
confidence: 98%
“…In the development of management strategies, management strategy evaluation (MSE) is often used to evaluate the potential different strategies that can influence the states of fish resources and their corresponding fisheries (Punt and Hobday, 2009). The MSE simulates the behaviour of fish stocks and fishing fleets and provides the ability to forecast, with estimates of the associated uncertainty, changes in the states of the fish stock and its fishery as a consequence of management scenarios.…”
Section: Conventional Fisheries Management Processmentioning
confidence: 99%